2008
DOI: 10.1175/2007jtecha1031.1
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Tropical Precipitating Systems Using Wind Profiler Spectral Moments. Part I: Algorithm Description and Validation

Abstract: The lower atmospheric wind profiler (LAWP) measurements made at Gadanki, India, have been used to develop an objective algorithm to classify the tropical precipitating systems. A detailed investigation on the existing classification scheme reveals major shortcomings in the scheme. In the present study, it is shown with examples that the Doppler velocity gradient (DVG) criterion is a necessary but certainly not a sufficient condition to identify the radar bright band. Such gradients in Doppler velocity can exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Therefore, if the height of melting level is different in these seasons, it may cause some differences in rain DSD at the surface. However, Rao et al (2008) found no significant difference in the height of the melting level from SW to NE monsoon at Chennai (120 km away from Gadanki). But the surface temperature and convective activity are different in these seasons.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, if the height of melting level is different in these seasons, it may cause some differences in rain DSD at the surface. However, Rao et al (2008) found no significant difference in the height of the melting level from SW to NE monsoon at Chennai (120 km away from Gadanki). But the surface temperature and convective activity are different in these seasons.…”
Section: Discussionmentioning
confidence: 74%
“…Though Gadanki receives 55 % of the annual rainfall in the southwest monsoon, raising instantaneous soil moisture levels, the high insolation and temperatures immediately consume the soil moisture for latent heating. On the other hand, this region also gets a good amount of rainfall during the cool northeast monsoon (Rao et al, 2009). The soil moisture levels, therefore, remain high in this season.…”
Section: Discussionmentioning
confidence: 98%
“…This site is located ∼ 375 m above the mean sea level in a rural area in southeastern peninsular India and is surrounded by hillocks (300-800 m within a 10 km region) distributed in a complex fashion. The rainfall in this region is influenced primarily by two monsoons, southwest (June-September) and northeast (OctoberDecember) (Rao et al, 2009). Summer and winter are the other two seasons, covering the months of March-May and January-February, respectively.…”
Section: Data and Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stratiform and convective rain can be distinguished by using Z or R values or by combining any of these parameters (see Rao et al 2008b for various classification schemes). For the present study, a reflectivity threshold of 40 dBZ (same as that used by ground-and space-borne radars) is employed to delineate stratiform and convective rain regimes.…”
Section: Methodsmentioning
confidence: 99%